Ijtihad view of foremost and later jurists and evaluation of modern concepts - Dr. Nabeela Falak (jihat-ul-islam, 2021)
In the present day, Muslim has been polarized in to two groups, traditional lists and modernists. Both, having their own ideology, are absolutely refuting each other in the basic concept of Islam. In this research paper, the research question is that is either ijtihad said to the modification , amendment and addition to Quran and Sunnah or pursuing Shariah ruling from the depth and the vastness of Quran and Sunnah.? Traditionalists point of view is that Whenever any new issue is raised about which there is no any clear solution or ruling present in the Shariah , then to derive the solution from the depth and Vastness of Quran and Sunnah is called ijtihad . Whereas according to modernists, ijtihad means addition, amendments, modification and reformation of Islamic Shariah. In this article meaning of ijtihad is describe according to the traditional Fuqha and the fuqha came terminally after them along with the contemporary concepts.an analysis is given at the end and tried to give the real and original concept of ijtihad.